Future Perspectives on Orthodox-Catholic Dialogue on the basis of current documents of the Great and Holy Synod of Crete - Moga, Ioan 1979- (2018)
The article deals with the ecclesiological challenges that rose after the Holy and Great Council of the Orthodox Church in Crete (June 2016) following the encounter between East and West, as far as the orthodox-catholic dialogue is concerned. The conciliar restrictive formulations (included in the document Relations of the Orthodox Church with the Rest of the Christian World) concerning the denomination of other Churches caused negative reactions from the roman-catholic side, which questioned the future of the dialogue with the Orthodox Church. From that perspective, this study analyses the above-mentioned document and some other documents of the Council in Crete and sketches future perspectives on the orthodox-catholic dialogue. The main thesis of the present study is that, considering the ecclesiological debates that were held in Crete and afterwards, it becomes obvious that the theological orthodox-catholic dialogue needs a restart, arising from the spirit of the beginnings (the so called plan for dialogue adopted in Patmos/Rhodes, 1980). Some of the premises for this restart should be: the liberation of church-political strategies, the emphasis of the spiritual relevance and responsibility of the inter-Christian dialogue and a deeper consideration and implementation of the theological results of the different regional or unofficial dialogue groups. The study finalizes with concrete proposals of alternative themes of reflection for overcoming the aporias that the official theological dialogue is dealing with.
Keywords: Church; Confession; Ecclesiology; Ecumenical Dialogue; Exclusivism; Orthodox Theology; orthodox-catholic dialogue; panorthodox synod; Holy and Great Council of the Orthodox Church (Crete 2016)